استخدام نموذج راش في تدريج مقياس سوء التكيف الدراسي من اختبار منيسوتا "MMPI-2 " لدراسة بعض العوامل المؤثرة على دقة القياس (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The current research aims to study the effectiveness of Rush model in the grading scale of poor school adjustment College Maladjustment test of the second version of Minnesota Multiphasic Personality Revision Minnesota test. It also aims to test the effectiveness of the sample of study on the results of the grading scale poor school adjustment using the accuracy Criteria of the standard error and stability and information function. The search results after staging reach a form Summary of the scale process saves time and effort after the staging process listed unit Logit so were some of the vocabulary is appropriate to exclude according to suitability index note that the deletion of the vocabulary has not been on a diagnostic basis, according to statistical values for Bilog, and therefore an instrument enjoy a high level of accuracy extend specialist holistic perspective for all effects and health problems and social and psychological responsible for poor school adjustment, note that access to treatment is successful but accurate assessment that gives reliable results in the treatment process. As it turns out that the best size of the sample in the staging process is (700) after any medium samples tested small samples (300) and large samples (2000) and in accordance with the Criteria for the three-precision, a standard error and stability and function information. يهدف البحث الحالي إلى دراسة مدى فعالية نموذج راش Racsh model في تدريج مقياس سوء التكيف الدراسي College Maladjustment test من اختبار منيسوتا النسخة الثانية Minnesota Multiphasic Personality Revision، واختبار أثر حجم العينة في نتائج تدريج مقياس سوء التكيف الدراسي باستخدام محكات الدقة المتمثلة بالخطأ المعياري والثبات ودالة المعلومات . فتمثلت نتائج البحث إثر عملية التدريج التوصل لشكل مختصر للمقياس يوفر الوقت والجهد بعد عملية التدريج مدرجاً بوحدة اللوجيت Logitبحيث تم استبعاد بعض المفردات غير الملائمة وفق مؤشر الملاءمة علماً أن حذف المفردات لم يتم على أساس تشخيصي وذلك وفق القيم الاحصائية الخاصة بالبايلوج Bilog، وبالتالي وجود أداة تتمتع بمستوى عال من الدقة تمد الأخصائي بمنظور شمولي عن كل المؤثرات والمشكلات الصحية و الاجتماعية و النفسية المسؤولة عن سوء التكيف الدراسي، علماً أن الوصول للعلاج الناجح إنما يتمثل في التقييم الدقيق الذي يعطي نتائج يمكن الاعتماد عليها في عملية العلاج. كما تبين أن أفضل حجم للعينة في عملية التدريج هو (700 ) أي العينات المتوسطة بعدما اختبرت العينات الصغيرة (300) و العينات الكبيرة (2000 ) وذلك وفقاً لمحكات الدقة الثلاث وهي الخطأ المعياري و الثبات و دالة المعلومات .